Penyakit Embun Tepung Dan Cara Pengendaliannya Pada Tanaman Kedelai Dan Kacang Hijau - Sumartini Sumartini; Mudji Rahayu (Badan Penelitian dan Pengembangan Pertanian, 2017)
Powdery mildew disease is caused by Erysiphae diffusa (Cook and Peck) fungi on soybeans and E. polygoni (DC Sawada) on mungbean. Both diseases are an important disease because of their widely spread and high yield loss, reaching 35% in soybeans and 26% in mungbean. In Indonesia, the disease occurs in central areas of soybean production and mungbean. The spread of the disease includes Asia, the United States of America , and Brazil. The symptoms of powdery mildew are easily recognizable in the presence of white flour on the top surface of the leaves. The intensity of powdery mildew is usually high in the dry season, when the temperature is cold in the morning and much mildew conditions around the plant. This situation will interfere with the process of photosynthesis and transpiration. In addition, Erysiphe’s haustorium absorbs plant nutrients that will interfere with some metabolic functions and processes. Control of powdery mildew will suppress the loss of grain bean and results nationally supports the availability of soybean and mungbean. Recommended control measures are spraying with plant materials (extracts of neem seeds, tea compost, cow´s whole milk, essential oil of citronella, lemongrass, eucalyptus, cinnamon, and tea tree) on the incidence of powdery mildew disease on soybean and the use of Vima1 varieties for control of powdery mildew disease on mungbean.Keywords: Soybean, mungbean, powdery mildew, control AbstrakPenyakit embun tepung disebabkan oleh cendawan Erysiphae diffusa (Cook and Peck) pada tanaman kedelai dan E. polygoni (DC Sawada) pada kacang hijau. Penyebaran penyakit penting ini menyebabkan kehilangan hasil mencapai 35% pada kedelai dan 26% pada kacang hijau. Di Indonesia, penyakit ini terjadi di sentra produksi kedelai dan kacang hijau. Di luar negeri, penyebaran penyakit embun tepung meliputi Asia, Amerika Serikat, dan Brazil. Intensitas penyakit biasanya tinggi pada musim kemarau, pada saat suhu dingin di pagi hari dan kondisi berembun di sekitar pertanaman. Gejala penyakit embun tepung mudah dikenali dengan ciri seperti tepung di permukaan atas daun. Hal ini dapat mengganggu proses fotosintesis dan transpirasi. Selain itu, haustorium Erysiphe menyerap nutrisi tanaman sehingga mengganggu beberapa fungsi dan proses metabolisme. Penyakit embun tepung perlu dikendalikan untuk menekan kehilangan hasil kedelai dan kacang hijau. Cara pengendalian yang disarankan adalah penyemprotan dengan bahan nabati (ekstrak biji mimba, kompos teh, susu sapi, minyak dari citronella, lemongrass, eucalyptus, cinnamon, dan tanaman teh) pada kedelai dan penggunaan varietas tahan Vima-1 pada kacang hijau.Kata Kunci: Kedelai, kacang hijau, penyakit embun tepung, pengendalian